Arginase Inhibitor in the Pharmacological Correction of Endothelial Dysfunction - Mihail V. Pokrovskiy; Mihail V. Korokin; Svetlana A. Tsepeleva; Tatyana G. Pokrovskaya; Vladimir V. Gureev; Elena A. Konovalova; Oleg S. Gudyrev; Vladimir I. Kochkarov; Liliya V. Korokina; Eleonora N. Dudina; Anna V. Babko; Elena G. Terehova (International Journal of Hypertension)
This paper is about a way of correction of endothelial dysfunction with the inhibitor of arginase: L-norvaline. There is an imbalance between vasoconstriction and vasodilatation factors of endothelium on the basis of endothelial dysfunction. Among vasodilatation agents, nitrogen oxide plays the basic role. Amino acid L-arginine serves as a source of molecules of nitrogen oxide in an organism. Because of the high activity of arginase enzyme which catalyzes the hydrolysis of L-arginine into ornithine and urea, the bioavailability of nitrogen oxide decreases. The inhibitors of arginase suppress the activity of the given enzyme, raising and production of nitrogen oxide, preventing the development of endothelial dysfunction.